2020
DOI: 10.4049/jimmunol.1900915
|View full text |Cite
|
Sign up to set email alerts
|

TCRs with Distinct Specificity Profiles Use Different Binding Modes to Engage an Identical Peptide–HLA Complex

Abstract: The molecular rules driving TCR cross-reactivity are poorly understood and, consequently, it is unclear the extent to which TCRs targeting the same Ag recognize the same off-target peptides. We determined TCR-peptide-HLA crystal structures and, using a single-chain peptide-HLA phage library, we generated peptide specificity profiles for three newly identified human TCRs specific for the cancer testis Ag NY-ESO-1 157-165-HLA-A2. Two TCRs engaged the same central peptide feature, although were more permissive at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…Although like conformation, the alanine scan profile and MagPix analysis revealed lower levels of peptide selectivity compared with the affinity-enhanced TCRs. To probe this discrepancy further, we developed an approach for the characterization of TCR peptide degeneracy using randomized pHLA libraries displayed on phage (50). We used this system to identify peptide motif preferences for the affinity-enhanced TCRs and TCR mimics that recognized W5 was selected by 3M4E5_T2 and 3M4E5_T3, it was not the dominant amino acid preference at this position, with phenylalanine (F) being preferred by both reagents (Figure 3, E-F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although like conformation, the alanine scan profile and MagPix analysis revealed lower levels of peptide selectivity compared with the affinity-enhanced TCRs. To probe this discrepancy further, we developed an approach for the characterization of TCR peptide degeneracy using randomized pHLA libraries displayed on phage (50). We used this system to identify peptide motif preferences for the affinity-enhanced TCRs and TCR mimics that recognized W5 was selected by 3M4E5_T2 and 3M4E5_T3, it was not the dominant amino acid preference at this position, with phenylalanine (F) being preferred by both reagents (Figure 3, E-F).…”
Section: Resultsmentioning
confidence: 99%
“…Panning using scHLA libraries. scHLA libraries were generated as previously described (50). Biotinylated affinity-enhanced TCRs (1G4_α 5 β 100 , 1G4_α 5 β 51 , and 1G4_α 58 β 61 ) and TCR-mimic antibodies (3M4E5, 3M4E5_T2, and 3M4E5_T3) were captured on streptavidincoated paramagnetic beads and incubated with the library of purified phage particles preblocked in 3% MPBS buffer.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it is likely that computational tools will sit alongside other experimental approaches to ensure that therapeutically deployed aeTCRs maintain peptide selectivity relative to their WT parent TCR. 46 …”
Section: Discussionmentioning
confidence: 99%
“…NY-ESO-1 157−165 (peptide sequence SLLMWITQC) has been demonstrated to be a safe and effective human leukocyte antigen (HLA)-A2 restricted antigenic epitope with therapeutic potency, which can be recognized by specific T cells (12). Several studies have identified and characterized the function of NY-ESO-1 157−165 specific TCRs (13)(14)(15), and >30% of TCR-T cell clinical trials have targeted NY-ESO-1 157−165 (16). Among these TCRs, 1G4, which has been extensively investigated, with clear recognition mechanisms with NY-ESO-1 157−165 (17,18), is currently undergoing multiple clinical trials for a range of advanced solid tumors (11), and striking clinical responses have been observed in patients with advanced multiple myeloma and synovial cell sarcoma (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%